Vibration energy-harvesting using inerter-based two-degrees-of-freedom system. (1st January 2021) - Liu, Mingyi; Tai, Wei-Che; Zuo, Lei
Highlights: Neglectable extra mass was added, while the advantage of 2DOF system is obtained. Larger power is obtained compared with SDOF counterpart with the same stroke limit.. Larger power is obtained in target frequency range compared with SDOF counterpart. Abstract: Rotary electromagnetic generators that have high power density, large power output, and large rotational inertia are increasingly used in vibration energy-harvesting systems. When applied to single-degree-of-freedom (SDOF) systems, it is found that the inertance reduces the system frequency bandwidth. Furthermore, the maximum power output of SDOF systems is limited by the mechanical damping and the maximum allowable stroke. Two-degrees-of-freedom (2DOF) energy-harvesting systems have been proposed in recent years and demonstrated to have larger power output and wider bandwidth compared with SDOF systems. However, a considerable additional physical mass has to be added to an SDOF system to create a 2DOF energy-harvesting system, which may increase the total weight and requires more space. By utilizing the rotational inertia of the electromagnetic generator and a line-to-rotation mechanism as inerter, an inerter-based 2DOF system that requires neglectable additional physical mass is proposed, in which a spring and an inerter are connected in series between the primary mass and the vibration base. Parameters including the mass ratio, the frequency tuning ratio, the spring ratio, and the damping ratio, were optimized for the inerter-based 2DOF system. Optimal specific power with stroke limitation was obtained. A benchmark test using an energy harvesting backpack was done to validate the analysis results. Both analyses and experimental tests show that the inerter-based 2DOF can have larger specific power and larger power-to-stroke ratio compared with its SDOF counterpart. The energy conversion efficiency is also improved. Compared with the conventional 2DOF system, the inerter-based 2DOF system is not only lightweight but also less sensitive to parameter changes.